The Role of Media in Shaping Language and Literature: A Critical Review - Yadav, Harshita (Journal of Advanced Research in English & Education; Vol 9 No 3 (2024): Journal of Advanced Research in English & Education, 2024)
The interplay between media, language, and literature has evolved significantly in the digital age, where multimedia platforms have become pivotal in shaping communication and narrative forms. In today's interconnected world, where digital technologies permeate everyday life, media serves as a dynamic space for the creation, dissemination, and transformation of language and literature. This review explores how media influences the development of language and literature, highlighting critical insights from theoretical frameworks and empirical research. Through the examination of various forms of media, including print, visual, digital, and social media, this article delves into the multifaceted ways media shapes linguistic practices and literary expression. The review also addresses how media fosters new forms of storytelling, interactivity, and audience engagement, shaping both the form and content of literature. Additionally, it discusses the power dynamics inherent in mediated communication, such as issues of representation, inclusion, and identity construction. By synthesizing scholarly perspectives from fields such as media studies, sociolinguistics, literary criticism, and cultural studies, this review offers a comprehensive understanding of how media impacts both language use and literary creation in contemporary society. Through this nuanced exploration, the article provides insights into the evolving relationship between media, language, and literature, highlighting the complexities of communication in the digital era.